A comparison between neurological clinical signs, cerebrospinal fluid analysis, cross-sectional CNS imaging, and infectious disease testing in 168 dogs with infectious or immune-mediated meningoencephalomyelitis from Brazil - Bach, Fernando Swiech; Cray, Carolyn; Burgos, Ana Paula; Junior, José Ademar Villanova; Montiani-Ferreira, Fabiano (Frontiers in Veterinary Science, 2023)
This retrospective study evaluated canine patients with presumptively diagnosed meningoencephalomyelitis (ME) based on neurological clinical signs, cerebrospinal fluid (CSF) analysis, cross-sectional imaging, and infectious disease testing with a limited neurological-focused polymerase chain reaction (PCR) panel performed on blood and CSF. The first goal was to determine the proportion of dogs where the condition was caused by an infectious agent versus a probable immune-mediated etiology (i.e., meningoencephalomyelitis of unknown origin; MUO) in our geographic region. Secondary goals of this study were to examine associations between abnormal CSF test results and cross-sectional neuroimaging findings, in addition to defining the age and most common neurological clinical sign in each group of ME. A total of 168 dogs matched the inclusion criteria. Presumptive MUO was observed in 152/168 (90.5%) of dogs and infectious ME was identified in 16/168 (9.5%) of dogs (p < 0.0001). Canine distemper virus (CDV) was the most common cause of infectious ME in 10/16 dogs (62.5%). Of the total cases with a positive infectious disease result, 3/16 (18.7%) had normal CSF results and 13/16 (81.3%) had abnormal CSF results (p = 0.0078). MRI and CT abnormalities in the brain were detected in 74% and 39% of dogs with inflammatory CSF, respectively. MRI and CT abnormalities in the spinal cord were detected in 90% and 50% of dogs with abnormal CSF results, respectively. Age was not significantly different between infectious ME and presumptive MUO groups (p=0.15). Seizures were the most common clinical sign reported for both MUO (36.8% of cases) and infectious ME (31.2% of cases). In conclusion, presumptive MUO is significantly more common than infectious ME in this population of dogs. Also, although normal CSF results was uncommon in dogs with infectious ME this finding occurred in several patients (3/16), suggesting that infectious disease testing should be considered even in the face of normal CSF results. Finally, MRI was more sensitive than CT in detection of abnormalities when dogs with ME had inflammatory CSF results but was not 100% sensitive, suggesting CSF analysis should be performed to rule-out inflammation even when no abnormalities are detected on MRI or CT.